1998
DOI: 10.1097/00006123-199811000-00039
|View full text |Cite
|
Sign up to set email alerts
|

Enoxaparin Increases the Incidence of Postoperative Intracranial Hemorrhage when Initiated Preoperatively for Deep Venous Thrombosis Prophylaxis in Patients with Brain Tumors

Abstract: Enoxaparin therapy initiated at the time of anesthesia induction increases postoperative intracranial hemorrhage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
143
1
6

Year Published

2000
2000
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 233 publications
(156 citation statements)
references
References 24 publications
5
143
1
6
Order By: Relevance
“…Prior studies have shown that prophylactic treatment with low molecular weight heparin leads to fewer vascular complications such DVT and VTEs [10][11][12][13][14][15]. However, the risk of postoperative hematoma has been shown to increase with early anticoagulation [16]. Some studies have evaluated the use of heparin or enoxaparin with different regimens and different doses and there is no good consensus for preferred postoperative anticoagulation regimen.…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies have shown that prophylactic treatment with low molecular weight heparin leads to fewer vascular complications such DVT and VTEs [10][11][12][13][14][15]. However, the risk of postoperative hematoma has been shown to increase with early anticoagulation [16]. Some studies have evaluated the use of heparin or enoxaparin with different regimens and different doses and there is no good consensus for preferred postoperative anticoagulation regimen.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the perception of high VTE rates among these patients might also impact clinical outcomes by leading to overly aggressive VTE prophylaxis. For instance, in a series of patients undergoing neurosurgery, Dickinson et al, 21 administered enoxaparin 30 mg subcutaneously every 12 hours, with the first dose given before surgery. Whereas preoperative DVT prophylaxis has demonstrated benefit in the highest-risk VTE populations, such as patients undergoing elective hip arthroplasty, 22 this study was terminated when 5 of 46 patients (11%) sustained clinically significant intracranial hemorrhage before administration of the second enoxaparin dose.…”
Section: Discussionmentioning
confidence: 99%
“…Data on this association have been mixed. Some studies have demonstrated an increased rate of intracranial hemorrhage when VTE chemoprophylaxis is initiated preoperatively [45]. Other studies have demonstrated no statistically significant association between the two [75][76][77][78].…”
Section: Prophylaxis Chemicalmentioning
confidence: 99%
“…Several studies have compared the effectiveness of chemical anticoagulation with the effectiveness of mechanical prophylaxis [7,32,36,45,52,74,82]. Many of these studies show that combined prophylaxis has a higher effectiveness in preventing VTE without increasing risk to the patient than either method alone ( …”
Section: Combined Prophylaxismentioning
confidence: 99%
See 1 more Smart Citation